PENERAPAN METODE ALGORITHMA FP-GROWTH DALAM PENENTUAN POLA PEMBELIAN KONSUMEN PADA TOKO TENUN UNGGAN LANSEK MANIH (INDRA YENI) DENGAN MENGGUNAKAN BAHASA PEMOGRAMAN PHP DAN DATABASE MYSQL - Elsa Nurhasanah (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2023)
Weaving is one of the cultural works produced in various regions throughout the archipelago. Increasing the weaving industry in various regions in Indonesia is an important effort to preserve the nation's cultural heritage as well as pride that reflects the identity of the Indonesian nation. The Unggan Lansek Manih (Indra Yeni) weaving shop is one of the weaving shops in Sijunjung district whose production system still uses manual methods, namely using human labor. Woven fabric production is carried out according to consumer orders. However, there is also the manufacture of ready-made woven fabrics for stock sales, which allows for business losses because if products that are rarely in demand by consumers are still being produced and then sold. One method that can be used to find data sets that frequently appear in a data set is the FP-Growth algorithm. The FP-Growth algorithm is an algorithm used to get patterns from a database. The application of the Fp-Growth Algorithm method designed using the PHP programming language and MySql DataBase at the Lansek Manih Unggan Weaving shop (Indra Yeni) aims to be able to create a system that can help determine the pattern of purchasing what products are often purchased by consumers at Unggan Weaving shops Lansek Manih (Indra Yeni) and minimize business losses.